2004
DOI: 10.1007/s00702-004-0187-y
|View full text |Cite
|
Sign up to set email alerts
|

Linalool suppresses voltage-gated currents in sensory neurons and cerebellar Purkinje cells

Abstract: Linalool is a major component of essential oils and possesses various biological effects in sensory or central nervous systems. To investigate the pharmacological and biophysical effects of linalool on voltage-gated currents in sensory neurons, we used the whole-cell patch clamp and the Ca(2+) imaging techniques. Under the voltage clamp, membrane depolarization generated time- and voltage-dependent current responses in newt olfactory receptor cells (ORCs). Linalool significantly and reversibly suppressed the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 17 publications
2
49
1
1
Order By: Relevance
“…(?60.0 mV at 24°C). The shape of waveforms, the I-V relationship, and the reversal potential were essentially the same as those obtained in previous work on newt ORCs [17].…”
Section: Electrophysiological Properties Of Voltage-gated Na Currentmentioning
confidence: 75%
“…(?60.0 mV at 24°C). The shape of waveforms, the I-V relationship, and the reversal potential were essentially the same as those obtained in previous work on newt ORCs [17].…”
Section: Electrophysiological Properties Of Voltage-gated Na Currentmentioning
confidence: 75%
“…Elisabetsky et al (1995) described that linalool inhibits glutamatergic neurons and later Sugawara et al (2000) observed that it also affected human brain beta waves amplitude. Earlier studies in newt olfactory receptor cells, newt retinal neurons and rat cerebellar Purkinje cells demonstrated that linalool non-selectively but reversibly suppressed the voltagegated currents (Narusuye et al, 2005). In the same report it was shown that linalool reduced KCl-induced intracellular Ca 2+ elevation without affecting the machinery responsible for intracellular Ca 2+ signaling (Narusuye et al, 2005).…”
Section: Constituents Of Essential Oils That Acts In the Central And mentioning
confidence: 94%
“…The local anaesthetic effects of carvones, as expressed by the inhibition of CAP, which is partially extinguished by nerve washing, could be a result of blockages of VGNaC, which is considered to be the main target of local anaesthetics [16,17]. The same mechanism has been proposed for the local anaesthetic action of linalool [18]. Yet another mechanism was proposed for the action of (−)-carvone, which was recently identified as a novel agonist of TRPV-1 channels [9], thus being a promising target for the development of analgesic drugs [10,11].…”
mentioning
confidence: 76%